PENGARUH KEPEMILIKAN INSTITUSIONAL, LEVERAGE DAN PROFITABILITAS TERHADAP MANAJEMEN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - BUDI UTAMI, LINA (Jurnal Akuntansi AKUNESA, 2019)
This research aimed to provide empirical evindence on the impact of institutional ownership, leverage and profitability and corporate governance on earning management. Good corporate governance is measured by managerial ownership. Discretionary accrual is the proxy of earnings management. This research used 98 companies listed in Indonesian stock exchange, selected using stratified sampling method, during the research periode 2015-2017. Data were analyzed using multiple regression method. Based on the result of anaysis concluded that independent variables of institutional ownership and leverage have not significant effect on earnings management. but profitability significant with earning management. Managerial ownership was also have not significant effect on earnings management, it means moderating variables can not strengthen or weaken the relationship of independent variables on the dependent variables.Keyword: Earnings Management, Good Corporate Governance, Institutional Ownership, Leverage, Profitability (ROA).